Nitric oxide scavengers based on o-phenylenediamine for the treatment of rheumatoid arthritis. (14th February 2023) - Lee, Yeong Mi; Lee, Sanggi; Kim, Won Jong
Abstract : We discovered an o -PD-based NO scavenger that is highly reactive with NO as an agent for RA treatment. We believe that the N-Me has potential applications for developing anti-inflammatory disease treatments targeting NO. Abstract : Nitric oxide (NO) plays various physiologically favorable roles in the body. However, excessive production of NO causes inflammation and leads to various chronic inflammatory diseases. A typical NO-related disease is rheumatoid arthritis (RA), and it is well known that NO is a critical molecule for inflammation in the pathophysiology of RA. Therefore, depletion of NO can be an attractive treatment option for RA. In this study, we proposed a new method to discover effective NO scavengers in the form of small molecules. o -Phenylenediamine ( o -PD), the core structure of the NO scavenger, is a diamino-aromatic compound that irreversibly reacts with NO through nucleophilic substitution of amine. Inspired by the nucleophilicity, we attempted to find new scavenger candidates by searching for conditions that increase the nucleophilicity of the amine moieties. Candidates were classified into the basic form o -PD, monoamine aniline, o -PD substituted with a nitro group, carboxyl group, and three methyl groups. The NO-scavenging ability of these candidates was demonstrated using the DAF-2 assay. N -Methyl- o -PD (N-Me) in the methyl (–CH3 ) group had the highest reactivity with NO among the candidates, and the efficiency of NO scavengers was confirmed in vitro and in vivo . Depleted levels of NO and reduced levels of pro-inflammatory cytokines by N-Me demonstrated remarkable therapeutic efficacy against joint damage and delayed severity in a collagen-induced arthritis (CIA) model. Therefore, our findings suggest that N-Me is a new NO scavenger with great potential for RA treatment and further clinical drug development.